Achieving progress in the writing classroom: Strengthening student writing with the help of the interactional process approach to teaching writing - Chambers, Gary (My University, 1999)
Teaching writing skills has generally been regarded as a problematic area of English teaching - a skill that has often been downgraded in the curriculum. The purpose of this thesis is to examine the ways in which a more considered understanding of writing skills and more creative approaches to teaching practice can help students to develop progress in writing. This thesis begins by defining the issues involved in producing the writing skill, the difficulties experienced in the writing classroom, and the approaches developed to teach writing. This thesis continues with an analysis of the beneficial insights provided to the writing teacher by research into discourse analysis, genre analysis, and error analysis. An error analysis study was conducted among a representative sample of students in the Department of English Language Teaching of Marmara University and the results recorded. These results revealed the need for a new type of teaching writing - the Interactional Process Approach (IPA) to writing was regarded as appropriate to meeting this aim. A representative cross-section of 50 second year undergraduate students from Marmara University's Department of English Language Teaching were selected to participate in a research process involving the three stage implementation of the IPA. The data produced by this research process was recorded, analysed, and evaluated. Results revealed the majority of students were able to improve their grammatical accuracy and language mechanics while fewer were able to improve their authoring skills. Further experimentation/ application of the IPA in the English language writing classroom in Turkey could prove highly beneficial.

Yazma becerilerinin öğretilmesi genellikle İngilizce öğretmenin sorunlu bir alanı olarak görülmektedir. Çoğu kez yazım becerilerine ders programlarında fazla önem verilmemektedir. Bu tezin amacı, öğrencilerin yazma becerilerinin gelişmesine yardımcı olacak, üzerinde daha çok düşünülmüş bir yazma becerileri anlayışının ve pratiğinin öğretilmesinde, daha yaratıcı yaklaşımların incelenmesidir. Bu tez, yazma becerilerinin geliştirilmesini, yazma sınıflarında yaşanan zorlukları ve yazmanın öğretilmesinde geliştirilen yaklaşımları içeren konuları tanımlamakla başlamaktadır. Tez, yazma öğreticisine yararlı bakış açıları sağlayacak Yazma ve Konuşma Analizini (Discourse Analysis), Tür Analizini (Genre Analysis) ve Hata Analizini (Error Analysis) içine alan analizi irdelemekle devam etmektedir. Daha sonraki bölümde, Marmara Üniversitesi İngiliz Dili Eğitimi bölümündeki öğrenciler arasından seçilen bir grup öğrenci arasında hata analizi çalışması yapılmış ve bu çalışmanın sonuçlar açıklanmıştır. Bu sonuçlar yazmanın öğretilmesinde yeni bir modele ihtiyaç duyulduğunu göstermiş ve Karşılıklı Etkileşim Süreci Yönteminin (Interactional Process Approach - IPA) bu amaca uygun bir model olabileceği düşünülmüştür. Marmara Üniversitesi İngiliz Dili Eğitimi Bölümü ikinci sınıf öğrencilerinden 50 öğrenci, yöntemin yerine getirilmesindeki üç aşamanın araştırılmasına katılmak üzere seçilmiştir. Bu araştırma sürecinde oluşan veriler kaydedilip analiz edilmiş ve değerlendirilmiştir.
Keywords: Dil; İNGİLİZ DİLİ; İngilizce; İngilizce’ nin yazı sistemi; YAZI SİSTEMİ